2020
DOI: 10.1186/s13756-020-00840-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CMY-type beta-lactamases in Escherichia coli isolates from paediatric patients in a tertiary care hospital in Mexico

Abstract: Background The aim of this study was to detect CMY-type beta-lactamases in E. coli isolates obtained from paediatric patients. Methods In total, 404 infection-causing E. coli isolates resistant to third and fourth generation cephalosporins (3GC, 4GC) were collected from paediatric patients over a 2 years period. The identification and susceptibility profiles were determined with an automated microbiology system. Typing of blaCMY and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Previous studies show that bla SHV is responsible for resistance to penicillins such as ampicillin and piperacillin [ 42 ]. bla CMY is a type of AmpC plasmid that may cause antibiotic resistance to ceftazidime, cefotaxime, cefoxitin, azetronam and probably cefepime [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that bla SHV is responsible for resistance to penicillins such as ampicillin and piperacillin [ 42 ]. bla CMY is a type of AmpC plasmid that may cause antibiotic resistance to ceftazidime, cefotaxime, cefoxitin, azetronam and probably cefepime [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed a high diversity of E. coli isolates circulating at the Cerdanya Hospital according to MLST and phylogenetic analysis, as well as the presence of the high-risk clones ST131, ST405, and ST10 [ 7 , 52 ]. Similar to previous reports from Tanzania [ 32 ] and Spain [ 53 ], the most common clonal complexes were ST10 and ST131, both carriers of CTX-M-14 and CTX-M-15 as the main ESBLs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its spread by plasmids from different groups, the bla CMY-2 gene is commonly found in E. coli worldwide from human, animal, and environmental sources [29]. In North America, this gene is commonly found in E. coli from cattle [30] Additionally, it has been previously identified in pediatric patients in Mexico [31]. However, in this study, bla CMY-2 was identified not only in retail meat (47C) but also in E. coli that was isolated from humans (87CLU), emphasizing the transmission of bla CMY-2 from animals to humans.…”
Section: Discussionmentioning
confidence: 99%